Affective symptoms in professionals who work in the positive COVID-19 cases care - Yaima Alonso Cruz; Ivonne Cepero Rodríguez; Lucia del Carmen Alba Pérez; Vivian Pérez de la Cruz; Leidiana Escobedo Sánchez (Medisur)
Background: COVID-19 involves specific challenges for healthcare workers, which represent a greater burden of stress. This confers interest and relevance to the study of the affective sphere in this sector, a protagonist in the positive COVID-19 patient’s care. Objective: to characterize affective symptoms in professionals who work in the positive COVID-19 cases care. Methods: a cross-sectional descriptive study was carried out in health professionals who work in the positive COVID-19 patient’s care; between April and July 2020, at the Manuel Fajardo Rivero hospital in Santa Clara. 82 workers (nurses and health technologists) were the study population. The variables studied were sex, professional category and range of severity of affective symptoms (depression and anxiety). Results: all the professionals presented some degree of anxiety, with a predominance of the moderate form (64.6%). The 63.4% did not show depression, however, 43.47% of those who had this symptom were women, and 52.63% were professional nurses. Anxiety moderately affected 72.22% of men, 58.69% of women, and 68.42% of nurses. Conclusion: Among the affective symptoms in professionals who work in the positive COVID 19 cases care, a predominance of anxiety was observed. This study explores aspects of mental health that foresee the importance of future interventions.